Book Review : INTERCULTURAL LANGUAGE TEACHING AND LEARNING - Kaswan Kaswan (Eltin Journal : Journal of English Language Teaching in Indonesia, 2013)
The analysis of language and culture has been long and widely made.  To mention a few, Lies Sercu (2005) addresses this issue in Foreign Language Teachers and Intercultural Competence,  Soler and Jordan (ed, 2007) in Intercultural language Use and Language Learning, Nieto (2010) in Language, Cultural and Teaching, and Deardorff (2009) in The Sage Handbook of Intercultural Competence . Nevertheless, most recently this topic has  received  more attention  and  become more important,  as  discussed    by   Dasep Suprijadi and Euis Rina Mulyani in their research based articles.  If the goal of language instruction is communicative competence, language instruction must be integrated with cultural and cross-cultural instruction for sociocultural competence is part of   communicative competence, besides linguistic competence, discourse   competence,   formulaic   competence,   and   interactional   competence,   as proposed by Celce-Murcia (1995) in Soler and Jorda (2007). Sociocultural competence refers to the speaker’s pragmatic knowledge, i.e. how to express messages appropriately within  the  overall  social  and  cultural  context  of  communication.  This  includes knowledge of   language variation with reference to sociocultural norms of the target language. In fact a social or cultural blunder can be far more serious than a linguistic error when one is engaged in oral communication.